From a niche to the norm: a framework for action to empower collaborative education research - Oyewole, Kemi A.; Resnick, Alison Fox; Farrell, Caitlin C.; Wentworth, Laura; Furtak, Erin Marie; Borko, Hilda; Wright, Kim; Weiss, Jane C.; Arce-Trigatti, Paula (Frontiers in Education, 2025)
Educational leaders and researchers have stressed the value of centering communities in research. Yet, substantive research collaborations have remained the exception rather than the rule. Critical, organizational, and learning theories suggest the need to modify research systems, organizations, and infrastructure for the broad adoption of collaborative paradigms. We present a framework for normalizing collaborative research in the field of education: a desire for research impact animates these changes and will require actions that support egalitarian funding, power-leveling design, deliberate learning opportunities, expansive communication, and justice-aligned incentives. We build on the work of the Collaborative Education Research Collective to explore our framework through a sample of eight researchers’ vignettes describing their collaborative learning experiences. We find that authors center their narratives on individually compelling experiences with research impact, design, and learning opportunities. However, less emphasized action areas of our framework—funding, communication, and incentives—highlight the importance of expanding from individual to organizational change. Our findings and illustrative examples serve as a charge to proactively advance the role of research in creating more liberated educational futures.